2001
DOI: 10.1079/bjn2000223
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the fatty acid composition of muscle and adipose tissue in beef cattle

Abstract: Enhancing the n-3 polyunsaturated fatty acid (PUFA) content of beef is important in view of the generally saturated nature of fatty acids in ruminant meats and the negative effect this can have on human health. This study examined the effects of different sources of dietary n-3 PUFA on the performance of steers and the fatty acid composition of m. longissimus thoracis muscle and associated subcutaneous adipose tissue. Animals were fed ad libitum on grass silage plus one of four concentrates (60:40 forage:conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
287
10
9

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(360 citation statements)
references
References 34 publications
38
287
10
9
Order By: Relevance
“…According to that, meat from all treatment groups would be well accepted by consumers, even after 14 days of storage. When animals are fed with a similar basal diet, but fatty acid composition is altered by the addition of different fats to the diet, lipid and colour stability can be expected to be more related to the fatty acid composition than to the antioxidant concentration (Scollan et al, 2001). From the initial exposure to oxygen, all the measurements increased until day 1, but thereafter lightness remained stable, while redness, yellowness, hue and Chroma gradually decreased, especially after 5 days of storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to that, meat from all treatment groups would be well accepted by consumers, even after 14 days of storage. When animals are fed with a similar basal diet, but fatty acid composition is altered by the addition of different fats to the diet, lipid and colour stability can be expected to be more related to the fatty acid composition than to the antioxidant concentration (Scollan et al, 2001). From the initial exposure to oxygen, all the measurements increased until day 1, but thereafter lightness remained stable, while redness, yellowness, hue and Chroma gradually decreased, especially after 5 days of storage.…”
Section: Resultsmentioning
confidence: 99%
“…CLA is a group of naturally occurring fatty acid isomers found in some foods such as beef and other ruminant products (Ritzenthaler et al, 2001). During ruminal biohydrogenation of dietary unsaturated lipids, unique fatty acid intermediates including CLA and trans-vaccenic acid, are produced in addition to saturated end products (Scollan et al, 2001). However, the CLA content of beef may also be increased by feeding rumen protected CLA supplements, making CLA available for absorption in the intestine and deposition in tissues (Poulson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of investigations on ruminal PUFA-biohydrogenation is to create healthier ruminant products with low saturated fatty acid and high n-3 fatty acid contents (Scollan et al 2001;Jenkins et al 2008), and with potentially health-promoting CLA, mainly cis-9,trans-11-CLA. Considerable progress has been made in tracing intermediates of linoleic acid biohydrogenation.…”
Section: Discussionmentioning
confidence: 99%
“…Conjugated 18:3 is regarded as an intermediate of PUFA-biohydrogenation occurring in the rumen, which affects the fatty acid compositions of dairy products. Understanding of the PUFA-biohydrogenation process in the rumen is important for improving the fatty acid profiles of diary products so as to be rich in n-3 polyunsaturated fatty acids and CLA (Scollan et al 2001;Jenkins et al 2008). With respect to this, α-linolenic acid transformation by rumen bacteria was investigated and it was found that cis-9, trans-11,cis-15-18:3 is an initial intermediate, which is further transformed into trans-11,cis-15-octadecadienoic acid (18:2) and then to trans-11-octadecenoic acid (18:1).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of fish oil (FO), in the diet of ruminants, enhances the concentration of C20:5n-3 and C22:6n-3 in milk (Offer et al, 1999;Shingfield et al, 2003;Loor et al, 2005a) and muscle (Scollan et al, 2001a;Kook et al, 2002). FO is also known to inhibit the complete biohydrogenation of C18 PUFA to C18:0 resulting in an accumulation of trans-11 C18:1 (Shingfield et al, 2003, Lee et al, 2005, Loor et al, 2005b.…”
Section: Introductionmentioning
confidence: 99%